Biodegradable and Electroactive Regenerated Bacterial Cellulose/MXene (Ti3C2Tx) Composite Hydrogel as Wound Dressing for Accelerating Skin Wound Healing under Electrical Stimulation. Issue 19 (31st August 2020) - Mao, Lin; Hu, Sanming; Gao, Yihua; Wang, Li; Zhao, Weiwei; Fu, Lina; Cheng, Haoyan; Xia, Lin; Xie, Shangxian; Ye, Weiliang; Shi, Zhijun; Yang, Guang
Abstract: Traditional wound dressings mainly participate in the passive healing processes and are rarely engaged in active wound healing by stimulating skin cell behaviors. Electrical stimulation (ES) has been known to regulate skin cell behaviors. Herein, a series of multifunctional hydrogels based on regenerated bacterial cellulose (rBC) and MXene (Ti3 C2 T x ) are first developed that can electrically modulate cell behaviors for active skin wound healing under external ES. The composite hydrogel with 2 wt% MXene (rBC/MXene‐2%) exhibits the highest electrical conductivity and the best biocompatibility. Meanwhile, the rBC/MXene‐2% hydrogel presents desired mechanical properties, favorable flexibility, good biodegradability, and high water‐uptake capacity. An in vivo study using a rat full‐thickness defect model reveals that this rBC/MXene hydrogel exhibits a better therapeutic effect than the commercial Tegaderm film. More importantly, in vitro and in vivo data demonstrate that coupling with ES, the hydrogel can significantly enhance the proliferation activity of NIH3T3 cells and accelerate the wound healing process, as compared to non‐ES controls. This study suggests that the biodegradable and electroactive rBC/MXene hydrogel is an appealing candidate as a wound dressing for skin wound healing, while also providing an effective synergistic therapeutic strategy for accelerating wound repair process through coupling ES with the hydrogel dressing. Abstract : In this work, a kind of novel multifunctional rBC/MXene composite hydrogel is first constructed by physical and chemical dual crosslinking. This electroactive hydrogel is an appealing candidate as a wound dressing for skin wound healing, while also realizing a local delivery of electrical stimulation at the wound site to electrically regulate skin cell behaviors for accelerating the wound healing process.